2018
DOI: 10.18805/ajdfr.dr-1314
|View full text |Cite
|
Sign up to set email alerts
|

Studies on sensory attributes and microbial analysis of stored osmo dehydrated bilimbi (Averroha bilimbi)

Abstract: A study was undertaken during 2015-2017 to study the sensory evaluation and microbial analysis of selected osmo dehydrated bilimbi treatments during storage. Osmo dehydrated bilimbi in 600Brix for 180 minutes and 80 0Brix for an immersion time of 120 and 180 minutes were packed using polypropylene packaging material and stored at ambient temperature for a period of four months. Minimum fungal count (2.42 cfu/g) and bacterial count (2.53 cfu/g) was recorded for bilimbi osmosed in 800B for 180 minutes. Bilimbi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Osmotic treatment at 80B for 180 minutes was found as the best treatment for Effect of Osmo Dehydration on Quality Attributes of Bilimbi (Averroha bilimbi) Fruits development of osmo-dehydrated bilimbi as it retained the stability and biochemical quality during storage. According to Aparna et al (2018) osmodehydrated bilimbi fruits were found to be microbiologically stable for a period of for months.…”
Section: Storage Studiesmentioning
confidence: 99%
“…Osmotic treatment at 80B for 180 minutes was found as the best treatment for Effect of Osmo Dehydration on Quality Attributes of Bilimbi (Averroha bilimbi) Fruits development of osmo-dehydrated bilimbi as it retained the stability and biochemical quality during storage. According to Aparna et al (2018) osmodehydrated bilimbi fruits were found to be microbiologically stable for a period of for months.…”
Section: Storage Studiesmentioning
confidence: 99%